Spaces S^p with Nonsymmetric Metric - Rukasov, V. I.; Stepanets, O. I. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We determine exact values of the best approximations and Kolmogorov widths of q-ellipsoids in spaces S_φ ^p,μ defined by anisotropic metric.